2015
DOI: 10.1186/s13000-015-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological grading of breast ductal carcinoma In Situ: validation of a web-based survey through intra-observer reproducibility analysis

Abstract: BackgroundHistopathological grading diagnosis of ductal carcinoma in situ (DCIS) of the breast may be very difficult even for experts, and it is important for therapeutic decisions. The challenge may be due to the inaccurate and/or subjective application of the diagnosis criteria. The aim of this study was to investigate the intra-observer agreement between a traditional method and a developed web-based questionnaire for scoring breast DCIS.MethodsA cross-sectional study was carried out to evaluate the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Several studies have looked at the consistency of grading or prognostically classifying DCIS, and generally found that these DCIS classifications were moderately reproducible, while a few others suggested worse or somewhat better agreement (Supplementary Table 2 and Fig. 4 representing it) [6,19,20,[30][31][32][33][34][35][36][37][38][39]. This degree of interobserver variability is also reflected by a recent analysis of nearly 5000 DCIS diagnosed during a period of 4 years in the Fig.…”
Section: Reproducibility Of Classifying Dcismentioning
confidence: 94%
See 2 more Smart Citations
“…Several studies have looked at the consistency of grading or prognostically classifying DCIS, and generally found that these DCIS classifications were moderately reproducible, while a few others suggested worse or somewhat better agreement (Supplementary Table 2 and Fig. 4 representing it) [6,19,20,[30][31][32][33][34][35][36][37][38][39]. This degree of interobserver variability is also reflected by a recent analysis of nearly 5000 DCIS diagnosed during a period of 4 years in the Fig.…”
Section: Reproducibility Of Classifying Dcismentioning
confidence: 94%
“…Nuclear grade 2 tiered (Cyto)nuclear grade 3 tiered WHO 2012 [6] Bethwaite [31] Agreement [39] Sneige [32] slight/missing (kappa 0-0.2) Sloane [33] fair (kappa 0.21-0.4 Sloane [33] moderate (kapa 0.41-0.6) Wells [34] substantial (kappa 0.61-0.8) Douglas-Jones [35] almost perfect (kappa >0.8) Gomes [36] empty cells Gomes [36] Schuh [37] van Bockstal [38] van Bockstal [38] Normal cells for comparative size [20] RBC RBC G1 [5,21,22,23,25 ] RBC/ductal epithelial cell nucleus G2 RBC/ductal epithelial cell nucleus G3 [3,4] RBC/ductal epithelial cell nucleus [24] No comparative size LORIS inclusion [18] Fig. 3 Comparative nuclear size described in some publications concerning the grading of DCIS.…”
Section: Further Inconsistenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…and stained with four different colors to allow a three-dimensional orientation. Nuclear grade was categorized according to the Van Nuys classification system (28). When the differential diagnosis was between ductal hyperplasia and low-grade DCIS, additional immunohistochemical staining (cytokeratin 5/6 and p63) was performed.…”
Section: Histologic Processingmentioning
confidence: 99%
“…In cancers, the shapes and types of cells present carry important diagnostic and prognostic information that are used to classify the tumor and assess how advanced a patient’s disease is. Manual evaluation of tissue histology by trained professionals is highly subjective, being prone to both considerable intra-observer and inter-observer variations [2]. The development of more objective quantitative metrics for evaluating pathology images remains a significant barrier in effectively using this resource in research and clinical care.…”
Section: Introductionmentioning
confidence: 99%